The Mediating Role of Customer Trust on the Relationships of Celebrity Endorsement and E-WOM to Instagram Purchase Intention - Firman, Ahmad; Ilyas, Gunawan Bata; Reza, Heru Kreshna; Lestari, Setyani Dwi; Putra, Aditya Halim Perdana Kusuma (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2021)
This study aims to reanalyze and reconfirm the relationships of celebrity endorsements and E-WOM on consumer purchasing intentions and examine the indirect influence of celebrity endorsements and e-WOM and trust as the mediation of purchase intentions. This study is the first in Indonesia to analyze the above mediating relationships. The data are from 100 Instagram users responding to online questionnaires and analyzed with PLS-SEM. The results showed that celebrity endorsement and e-WOM positively influence consumer confidence and purchasing intentions by mediating trust variables. This research highlights the role of influence in creating positive buzzes to the promoted sales.